2017
DOI: 10.4236/ce.2017.83037
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Attitudes towards Mathematics, and Metacognitive Awareness on Mathematics Achievements

Abstract: The aim of this study was to investigate the influence of attitudes towards mathematics and metacognitive awareness on mathematics achievement of high school students. In addition, this study interested in examining gender differences on mathematics achievement. The respondents of this study were 103 students of a senior high school in Tangerang, Indonesia. Attitudes Towards Mathematics Inventory (ATMI) was used to measure students' attitudes towards mathematics, and Metacognitive Awareness Inventory (MAI) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 14 publications
5
26
0
7
Order By: Relevance
“…Other variables which are important predictors of Turkish students' mathematics achievements are attitudes towards school, math anxiety and mathematics self-concept. Similarly, in other studies, it is found that attitudes towards school (Ajisuksmo & Saputri, 2017;Geesa et al, 2019;Lipnevich, Preckel, & Krumm, 2016), mathematics anxiety (Gunderson et al, 2018;Passolunghi et al, 2016) and mathematics self-concept (Chiu, 2017;Lee & Kung, 2018;Susperreguy et al, 2018) are significant predictors of mathematics achievement.…”
Section: Discussionsupporting
confidence: 64%
“…Other variables which are important predictors of Turkish students' mathematics achievements are attitudes towards school, math anxiety and mathematics self-concept. Similarly, in other studies, it is found that attitudes towards school (Ajisuksmo & Saputri, 2017;Geesa et al, 2019;Lipnevich, Preckel, & Krumm, 2016), mathematics anxiety (Gunderson et al, 2018;Passolunghi et al, 2016) and mathematics self-concept (Chiu, 2017;Lee & Kung, 2018;Susperreguy et al, 2018) are significant predictors of mathematics achievement.…”
Section: Discussionsupporting
confidence: 64%
“…In the midst of this, understudies should even now have an inspirational disposition towards it because, as indicated by Guner (2012), past investigations on science detailed that mentalities towards arithmetic have a primary job in deciding learning accomplishment. Ajisuksmo and Saputri (2017) referenced that the demeanors of the understudies influence their intellectual exercises. By having an inspirational frame of mind towards arithmetic, the understudies will feel that science is necessary with the goal that they will attempt to improve their arithmetic learning accomplishment.…”
Section: Frameworkmentioning
confidence: 99%
“…The Trend International Mathematical Science Study Advanced (TIMMS) examined patterns of students' achievement in mathematics and found out that for over 20 years, there were some declines in the students' performances, and there were no improvements in the countries assessed (Maltese & Tai, 2011). In the case of Indonesia, the PISA report (2012) showed that the achievement scores of Indonesian students in mathematics are recorded very low and was ranked the 64th out of 65 countries (Ajisuksmo & Saputri, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…emotional and beliefs), behaviour and cognitive (Ayob & M. Yasin, 2017). Positive attitude towards mathematics affect students willingness to learn mathematics compared with students with negative mathematics attitude, and once they feel that mathematics is important, they will try to improve their mathematics achievement (Ajisuksmo & Saputri, 2017). In the context of this study, students' attitude toward mathematics was evaluated from four aspects, namely, self-confidence, value, enjoyment, and motivation.…”
Section: Introductionmentioning
confidence: 99%